Nutrition-and gender-sensitive agri-food systems in the Mekong Delta, Cambodia: A case study of three interventions - Chuon, Sophea; Umali, Diana Jean A.; Or, Thy; Gonsalves, Julian; Nabuuma, Deborah; Pham, Huong; Duong, Thanh; Huynh Thi, Tuyen (2023)
This case study assessed three nutrition- and gender-sensitive agri-food systems interventions in the Mekong Delta to understand how the interventions support equitable and sustainable consumption and production of nutritious foods; and identify opportunities and gaps to increase equitable and sustainable consumption and production and consumption of nutritious foods in the Mekong Delta region of Cambodia. In this study, three projects in the Mekong Delta were studied: (i) the project implemented by WorldFish Cambodia, (ii) Helen Keller International’s project, and (iii) the project of Heifer International Cambodia.